PERBANDINGAN HASIL BELAJAR MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) DAN MODEL MAKE A MATCH PADA MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAIYAH - Riris Nurkholidah Rambe (JURNAL TEMATIK, 2019)
The problem examined in this study is the low student learning outcomes in the third semester of PGMI UIN North Sumatra. This study aims to determine the style of student learning outcomes can change the motion of an object in science courses by using the Contextual Teaching and Learning Learning Model (CTL) in the third semester of PGMI UIN North Sumatra students. The population in this study were all semester III students of PGMI UIN North Sumatra, amounting to 64 people who were divided into two classes. And the sample in this study were all members of the population or a total sample of 64 students. This type of research used in this research is a quasi experiment (quasi-experimental) using CTL model with a test data collection tool. Student learning outcomes using the CTL Model in natural science subjects have an average value of 81.83 while student learning outcomes using the Make A Match Learning Model in natural science subjects have an average value of 74.15. So it can be concluded that student learning outcomes in science subject matter Style Can Change the Motion of an Object using the Contextual Teaching and Learning (CTL) Model better than using the Make A Match Learning Model in the third semester of PGMI UIN North Sumatra.